COMT Val158Met Polymorphism and Social Impairment Interactively Affect Attention-Deficit Hyperactivity Symptoms in Healthy Adolescents - Millenet, Sabina K.; Nees, Frauke; Heintz, Stefan; Bach, Christiane; Frank, Josef; Vollstädt-Klein, Sabine; Bokde, Arun; Bromberg, Uli; Büchel, Christian; Quinlan, Erin B.; Desrivières, Sylvane; Fröhner, Juliane; et al. (Frontiers in Genetics, 2018)
The dopaminergic system has been shown to have substantial effects on the etiology of attention-deficit hyperactivity disorder (ADHD). However, while some studies found a significant direct effect, others did not. In this context, social behavior might play an important role as a factor that is related both to the dopaminergic system and ADHD. In a large epidemiological sample of healthy adolescents (N=462; 16-17 years), we assessed the level of ADHD symptoms using the Strengths and Difficulties Questionnaire, social behavior using the Social Responsiveness Scale, and the allelic distribution of the dopaminergic Catechol-O-methyltransferase (COMT) Val158Met polymorphism. We found a significant association between COMT and social impairment, insofar as Met-allele carriers showed increased levels of social impairment. Moreover, social impairment significantly determined an association between COMT and ADHD (explained variance: 19.09%). This effect did not significantly differ between males and females. COMT and social impairment might interactively affect ADHD symptomatology, and could thus represent significant gene-phenotypic risk factors for ADHD symptomatology. This might have interesting implications for prevention and intervention strategies with a focus on social behavior in genetically at-risk individuals.